Development of Corneal Astigmatism (CA) according to Axial Length/Corneal Radius (AL/CR) Ratio in a One-Year Follow-Up of Children in Beijing, China - Fenglei Wang; Lin Xiao; Xuxia Meng; Ling Wang; Dabo Wang (Journal of Ophthalmology)
Purpose. The correlations between the axial length-to-corneal radius (AL/CR) ratio and corneal astigmatism (CA) were studied by prospectively analyzing and comparing survey data from school children in the Beijing urban area from 2014 to 2015. Methods. In this longitudinal study, a total of 2,970 students were enrolled in 2014, and 2,179 students were enrolled in 2015. The students were in grades 1 and 4 of primary schools located in the Yangfangdian district of Beijing. The students were examined using the standard logarithmic visual acuity chart for uncorrected visual acuity (UCVA) and IOLMaster for ocular components. Results. From 2014 to 2015, the students from grades 1 and 4 had significantly worse UCVA results, longer axial lengths (AL), and greater AL/CRs (p<0.001). The boys had a longer AL and corneal radius (CR) than the girls (p<0.001). A significantly higher rate of increased CA was observed for the students with increased AL/CR than for those with decreased or unchanged ratios (AL/CR for grade 1, X2 = 12.304, p=0.001; for grade 4, X2 = 29.044, p<0.001). In addition, with increased AL/CR over one year, the CA value of the students in grades 1 and 4 became significantly larger (grade 1, p=0.001; grade 4, p<0.001); moreover, the UCVA became worse (p<0.001). Conclusions. We found that UCVA and AL growth were affected by aging. An increase in the AL/CR ratio is a risk factor for the progression of corneal astigmatism for school children.